Hubungan Lingkungan Sebagai Sumber Belajar Siswa Terhadap Hasil Belajar Siswa di SMP Negeri 15 Ambon - Layata, Lidia Evanjelin; Leuwol, Ferdinand Salomo; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
This study examines the relationship between the school environment as a learning resource and students’ academic achievement in geography at SMP Negeri 15 Ambon. The empirical gap in utilizing real environments as educational media highlights the need for an ecopedagogical approach contextualized within island-based education. The purpose of this study is to identify the contribution of the learning environment to students’ academic improvement and to assess the effectiveness of experiential-based learning practices. Employing a quantitative correlational design, data were collected from 30 students and analyzed using the Pearson Product Moment test with SPSS version 22. The findings reveal a positive and significant correlation between the school environment and students’ learning outcomes (r = 0.674, p < 0.05). Empirical evidence indicates that students engaged in direct environmental interactions demonstrate enhanced conceptual understanding, motivation, and analytical competence. This study extends experiential learning and ecopedagogy theories into the Indonesian island education context.